TEORI MENGENAI PENCIPTAAN MANUSIA DALAM HADIS NABI; KAJIAN MA’ANIL HADIS - Muhammad Abduh Wahid (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2020)
The discourse between religion and science (science) is a classic issue that is still developing in the Western world in the form of secularism. However, Islam does not approach this scientific problem from that perspective because Alquran and Sunnah have provided a complete and perfect system that covers all aspects of human life. This includes the process of human creation. This paper will examine the Hadith Text About the Process of Man's creation and How the Interpretation of the Hadith according to Science. The author found that the Creation of man after the prophet Adam was created through several fertilization phases.